Three-Dimensional Reconstruction of a Full-Size GABAB Receptor - Nyporko, A.Yu.; Naumenko, A.M.; Golius, A.; Tsymbaliuk, O.V.; Shapoval, L.M.; Davidovska, T.L. (Нейрофизиология, 2015)
The three-dimensional (3D) pattern of a full-size GABAB receptor has been reconstructed using computer techniques. To simulate a real microenvironment for the GABAB receptor, the latter was embedded in the bilipidic membrane with the corresponding salt-water environment. Since homology modeling of the GABAB receptor is among the computational methods allowing one to predict 3D coordinates when experimental data are not available, we reconstructed the structure of a full-size GABAB receptor by stepwise homology modeling of individual subunit parts. The stability of receptor subunits was evaluated by calculating the molecular dynamics. It has been found that C-terminal domains of the intracellular receptor show a tendency toward compaction, and coiled-coil areas form a structure almost identical to that specified by crystallization of these fragments. The structure obtained can be applied for further examination of the structural mechanisms of GABAB receptor interaction with GABA agonists and antagonists. It is quite evident that molecular dynamics computations might be a valuable tool in probing details of the receptor function.